A lengyel-szovjet-orosz háború és a revízió 1920 - Polgár, Tamás (Közép-Európai Közlemények, 2010)
At the same time with the Peace Treaty of Trianon, an economic agreement between Hungary and France was signed by the Hungarian government in which they put significant economic options at the disposal of a French group of firms. In exchange, the Hungarian party received a French declaration which they interpreted as the possibility of a partial territorial revision. According to this, diplomatic attempts were made for the reacquisition of Sub-Carpathia and the establishment of a common Hungarian-Polish border. Meanwhile, the French Ministry of Foreign Affairs was aiming at a Polish-Hungarian-Rumanian confederation based on economics. The Hungarian and Polish parties had already started negotiations, but the Rumanian-Hungarian negotiations never took place. On the occasion of the meanwhile serious Polish-Soviet conflict, the Hungarian government aimed at the rearmament of the Hungarian army and the occupation of Sub-Carpathia arguing that the Czech army would not be able to defend the passes of the Carpathians. All attempts failed, but oddly enough, it was the time of Beneš‟s journey to Belgrade and Bucarest, which meant the birth of the Little Entente.